2012
DOI: 10.1021/jm3016393
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-Conjugated Pterins as Inhibitors of Ricin Toxin A

Abstract: Several 7-peptide-substituted pterins were synthesized and tested as competitive active-site inhibitors of Ricin Toxin A (RTA). Focus began on dipeptide conjugates, and these results further guided the construction of several tripeptide conjugates. The binding of these compounds to RTA was studied via a luminescence-based kinetic assay, as well as through X-ray crystallography. Despite the relatively polar, solvent exposed active site, several hydrophobic interactions, most commonly π-interactions, not predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
35
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 38 publications
4
35
0
Order By: Relevance
“…Assays that directly measure depurination activity for toxin detection and mitigation procedures were recently reviewed [ 29 , 30 ]. Here, we specifically review the assays, which identified differences in the activity of Stxs [ 31 ], differences in ribosome interactions of RTA [ 22 , 32 , 33 , 34 , 35 , 36 ], Stxs [ 21 , 22 , 37 ], TCS [ 23 , 26 ], and PAP [ 24 , 25 ], provided information about the downstream consequences of depurination, such as the ribotoxic stress response and apoptosis [ 38 , 39 , 40 ], allowed the use of RIPs as tools to probe the structure and function of the ribosomal stalk [ 41 ], provided information about the functional divergence of the ribosomal stalk P1-P2 dimers [ 42 ] and were useful in the search for RIP inhibitors [ 43 , 44 , 45 , 46 , 47 , 48 ]. We discuss the advantages and limitations of each method and explain how more sensitive assays can distinguish the differences in depurination activity and provide information about the kinetics and the mechanism of the depurination reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Assays that directly measure depurination activity for toxin detection and mitigation procedures were recently reviewed [ 29 , 30 ]. Here, we specifically review the assays, which identified differences in the activity of Stxs [ 31 ], differences in ribosome interactions of RTA [ 22 , 32 , 33 , 34 , 35 , 36 ], Stxs [ 21 , 22 , 37 ], TCS [ 23 , 26 ], and PAP [ 24 , 25 ], provided information about the downstream consequences of depurination, such as the ribotoxic stress response and apoptosis [ 38 , 39 , 40 ], allowed the use of RIPs as tools to probe the structure and function of the ribosomal stalk [ 41 ], provided information about the functional divergence of the ribosomal stalk P1-P2 dimers [ 42 ] and were useful in the search for RIP inhibitors [ 43 , 44 , 45 , 46 , 47 , 48 ]. We discuss the advantages and limitations of each method and explain how more sensitive assays can distinguish the differences in depurination activity and provide information about the kinetics and the mechanism of the depurination reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, point mutations and (or) oxidative damage of proteins can result in increased surface hydrophobicity of proteins and have been linked to several age-related proteinopathies 7 8 9 10 11 12 . As a result, there has been a growing interest and need for developing probes and methods for sensing protein surface hydrophobicity 13 14 15 16 17 as this can help to design better drug molecules based on surface properties 18 19 20 21 .…”
mentioning
confidence: 99%
“…An equal strategy as the one followed to find aldose reductase inhibitors (see previous Section , diabetes complications) was also used by the same research group against RTA. They synthesized several dipeptides and tripeptides conjugated to pterin‐7‐carboxamides and obtained good results in RTA inhibition assays, with IC 50 values ranging from 6 to 115 μM, with the tyrosine‐conjugated compound 78 being the most potent molecule (Table ) …”
Section: Other Activitiesmentioning
confidence: 99%